Sensory analysis of texture and appearance lip balm containing olive oil - Ab. Hadi, Hazrina; Ab Salam, Mohd Ghazali (2016)
The main phenolic compounds of olive oil included hydroxytyrosol, tyrosol and oleuropein are believed to have higher antioxidant activity and have moisturizing properties towards skin. Due to beneficial effects of the olive oil, it has been used as the main ingredient in the developed lip balm. Thus, the main objective in this study was to use of sensory analysis as a tool to evaluate the attributes in term of appearance and texture of the developed lip balm product. The lip balm was formulated using natural ingredients such as beeswax, olive oil, cocoa butter, shea butter, jejoba oil, natural preservative and essential oils. The sample were evaluated by 18 volunteers for smoothness, spreadability, initial drag, tackiness and grittiness, degree absorption, amount residue, color and odor, shininess, applicator tube and coverage. The stick formulation showed organoleptic properties with light yellow colour, rose odour and uniform appearance. The attributes in term of structure of lip balm demostrated respondents acceptance with higher “strongly agree” or “agree” for smoothness, speadability and initial drag attributes. These characteristics of lip balm were depended on the proportion of fatty acid; wax, butter and oil in the formulation. The lip balm formulated has acceptable characteristics in term of texture especially in smoothness, spreadability, initial drag and tackiness. Overall, the respondents were satisfied with the product and agree the product has potential to be marketed.